PENGARUH POSITIONING TERHADAP BRAND LOYALTY DENGAN BRAND TRUST SEBAGAI VARIBEL MEDIASI PADA PELANGGAN RESTORAN C-BEZT FRIED CHICKEN PAITON PROBOLINGGO - Muhammad Syarif Hidayatullah Elmas (UPT Penerbitan Universitas Jember)
The aim of this research is to know the effect of positioning brand, loyalty and the influence on customers’ Brand Trust at C’bezt fried Chicken in Paiton Probolinggo. This research used quantitative with 280 populations as respondents and 70 respondents as the sample. This research used a regression analysis linier of SPSS software. The results are, firstly there is effect among customers’ positioning of Brand Trust and C’Best Fried Chicken of Paiton Probolinggo although the result is not quite significant. It showed the significant 0.122 more than 5% of their reliance. Secondly, there is effect among brand trust on customers’ brand loyalty of C’Best Fried Chicken restaurant at Paiton Probolinggo, the result is 0,082 more than 5% of their reliance. Thirdly, there is directly effect from the positioning on brand loyalty to the customers’ C’Best Fried Chicken at Paiton Probolinggo which shows significant result. It shows that the level of significant is 0.001 smaller than 5% of reliance.